Performance of high-strength concrete composite columns subject to earthquake loading conditions - Deenihan, John Edmond (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2011)
Composite construction has been used in industry for decades due to superior load carrying capacity of the members compared with traditional reinforced concrete construction. A composite column is a structural member that uses a combination of concrete incorporating structural steel shapes, pipes or tubes with or without reinforcing steel to provide adequate load carrying capacity to axial loads or a combination of axial loads and bending moments. The interactive and integral behaviour between the concrete and structural steel makes the composite column a very cost effective and structurally efficient member.
Keywords: Civil Engineering, Ph.D.; Ph.D. Trinity College Dublin.